PENGARUH HUBUNGAN DEKAT AUDITOR DAN KLIEN TERHADAP INDEPENDENSI AUDITOR - Lisbeth, Nency; Ramadhan, Yanuar (Jurnal Ecoment Global, 2022)
Auditor independence is clearly defined in the Code of Ethics and Financial Reporting Auditing Standards. Independence should be interpreted as no one is interested in incentives, impacts, or audits. If the auditor follows the client's intentions, contrary to his discretion, the auditor's opinion is meaningless. The independence of the auditor can only be considered to be violated if the reporting auditor knows or should know of circumstances or relationships that could affect his independence. The accountant needs to make an independent assessment of whether the risk is significant and whether the risk of the situation or relationship can be measured through safeguards that reduce risk in exchange for approval or rejection of the contract. The purpose of this study was to determine whether the auditor-client relationship will affect auditor independence.